Mechanoresponsive Luminescent Molecular Assemblies: An Emerging Class of Materials. Issue 6 (13th October 2015) - Sagara, Yoshimitsu; Yamane, Shogo; Mitani, Masato; Weder, Christoph; Kato, Takashi
Abstract : The possibility to change the molecular assembled structures of organic and organometallic materials through mechanical stimulation is emerging as a general and powerful concept for the design of functional materials. In particular, the photophysical properties such as photoluminescence color, quantum yield, and emission lifetime of organic and organometallic fluorophores can significantly depend on the molecular packing, enabling the development of molecular materials with mechanoresponsive luminescence characteristics. Indeed, an increasing number of studies have shown in recent years that mechanical force can be utilized to change the molecular arrangement, and thereby the optical response, of luminescent molecular assemblies of π‐conjugated organic or organometallic molecules. Here, the development of such mechanoresponsive luminescent (MRL) molecular assemblies consisting of organic or organometallic molecules is reviewed and emerging trends in this research field are summarized. After a brief introduction of mechanoresponsive luminescence observed in molecular assemblies, the concept of "luminescent molecular domino" is introduced, before molecular materials that show turn‐on/off of photoluminescence in response to mechanical stimulation are reviewed. Mechanically stimulated multicolor changes and water‐soluble MRL materials are also highlighted and approaches that combine the concept of MRL molecular assemblies with other materials types are presented in the last part of this progress report. Abstract : Mechanoresponsive luminescence exhibited by molecular materials is an emerging topic in materials science. The background of this research field is described, and the concept of "luminescent molecular domino", turn‐on/off behavior, multicolor changes, and water‐soluble mechanoresponsive luminescent materials are reviewed. Approaches to covalently attach such materials to other materials are also introduced.